Taylor Swift style : fashion through the eras - Chapelle, Sarah (St. Martin's Griffin, 2024)
"Dazzling. Incomparable. Unforgettable. The definitive book of Taylor Swift's fashion evolution. This gorgeous hardcover edition has gilded gold edges, foiled cover accents and colored endpapers. For Taylor Swift, fashion and music go hand-in-hand-each playing a powerful role in shaping the narrative of this generation's most prolific storyteller. Red lipstick isn't just a makeup choice--it's the emblem of an era. A mini skirt isn't simply part of a cute outfit--it's a suit of armor. From cowboy boots to teetering heels, fairytale dresses to bleach-tinged tresses, and the many memorable moments in between, Taylor Swift Style tells the fashion story behind every single Taylor Swift album, tracing Swift's musical evolution along with her ever-changing personal style. From red carpet looks, to streetwear, to tour costumes, Sarah Chapelle of the successful Instagram and blog Taylor Swift Style, has spent more than a decade documenting Swift's fashion choices and the intention behind each ensemble. Her deep dives into songs, lyrics, and behind-the-scenes insights paint a portrait of a megastar who knows exactly what she is doing. Taylor Swift Style seeks to explain the 'why' behind Swift's outfits--the Easter Eggs and deeper meanings behind every hemline and haircut--that speak to the emotional context of each musical moment. With over two hundred photos dating from Swift's earliest days as a country singer in Nashville, up through the present as a renowned pop icon, paired with insightful commentary, Taylor Swift Style is a one-of-a-kind keepsake and a must-have for Swifties"--